Zengshengping improves lung cancer by regulating the intestinal barrier and intestinal microbiota - Sun, E.; Meng, Xiangqi; Kang, Zhaoxia; Gu, Huimin; Li, Mingyu; Tan, Xiaobin; Feng, Liang; Jia, Xiaobin (Frontiers in Pharmacology, 2023)
Abstract: Based on the “gut-lung axis” and from the perspective of “treating the lung from the intestine”, the objective of the present study was to research the effect of Zengshengping (ZSP) on the intestinal physical, biological, and immune barriers, and explore its role in the prevention and treatment of lung cancer. The Lewis lung cancer and urethane-induced lung cancer models were established in C57BL/6 mice. The tumor, spleen, and thymus were weighed, and the inhibition rate, splenic and thymus indexes analyzed. Enzyme-linked immunosorbent assay was used to detect inflammatory factors and immunological indicators. Hematoxylin and eosin staining was performed on tissues to observe histopathological damage. Immunohistochemistry and Western blotting were carried out to detect tight junction protein expression in colon tissues and expression of Ki67 and p53 proteins in tumor tissues. Finally, the feces of mice were collected to investigate the changes in intestinal microbiota using 16SrDNA high-throughput sequencing technology. ZSP significantly reduced tumor weight and increased the splenic and thymus indexes. It decreased expression of Ki67 protein and increased expression of p53 protein. The serum levels of interleukin (IL)-1β, IL-6 and tumor necrosis factor α were decreased. The concentration of secretory immunoglobulin A in the colon and the bronchoalveolar lavage fluid (BALF) were increased. ZSP significantly reduced the level of tight junction proteins such as ZO-1, Occludin and Claudin-1. The decrease in probiotic strains such as Akkermansia and the increase in pathogens such as norank_f_Muribaculaceae and norank_f_Lachnospiraceae in the intestine may be related to the occurrence of lung cancer. The quantity of Akkermansia was significantly increased (p < 0.05) and the quantities of norank_f_Muribaculaceae and norank_f_Lachnospiraceae were significantly decreased in the ZSP group (p < 0.05). Compared with the urethane-induced lung cancer mice, the results showed that ZSP significantly increased the diversity and richness of the intestinal microbiota in the Lewis lung cancer mice. ZSP played an important role in the prevention and treatment of lung cancer by enhancing immunity, protecting the intestinal mucosa and regulating the intestinal microbiota.